Mismatch Between Education and Occupation: A Case Study of Pakistani Graduates. (The Pakistan Development Review, 2011)
In this study, an attempt has been made to estimate the incidences of job mismatch in Pakistan. The study has divided the job mismatch into three categories; education-job mismatch, qualification mismatch and field of study and job mismatch. Both the primary and secondary datasets have been used in which the formal sector employed graduates have been targeted. This study has measured the education-job mismatch by three approaches and found that about one-third of the graduates are facing education-job mismatch. In similar, more than one-fourth of the graduates are mismatched in qualification, about half of them are over-qualified and the half are under-qualified. The analysis also shows that 11.3 percent of the graduates have irrelevant and 13.8 percent have slightly relevant jobs to their studied field of disciplines. Our analysis shows that women are more likely than men to be mismatched in field of study. JEL classification: I23, I24, J21, J24 Keywords: Education and Inequality, Higher Education, Human Capital, Labour Market